COMPREHENSIVE MAPPING OF LAND SUBSIDENCE IN THE BANDUNG BASIN - Ilman Faqihuddin Anshorullah, Muhammad
The Bandung Basin is an area surrounded by Quatenary and Late Territorial volcanic mountains. Encompassing major cities such as Bandung, Cimahi, and parts of Sumedang Regency, the Bandung Basin has evolved into one of the regions with high economic, social, and political activites. However, due to these activities, the Bandung Basin experiences a phenomenon of significant land subsidence compared to several other cities in Indonesia. Land subsidence can occur due to excessive groundwater extraction, building loads, natural compaction, or other tectonic activities. The impact of land subsidence can lead to significant physical damage to buildings, roads, and bridges, ultimately resulting in economic losses. To monitor this phenomenon, various geodetic methods such as GNSS (Global Navigation Satellite System) surveys and InSAR (Interferometric Syntetic Aperture Radar) are used. GNSS survey results indicate that the rate of land subsidence in the Bandung Basin during the period of 2016-2023 ranges from 1.4 cm to 13 cm per year, while InSAR results show a range of 0.6 cm to 12 cm per year at the same locations. Although the dynamics of land subsidence are relatively small, they often go unnoticed by various parties. Therefore, a comprehensive dashboard presentation oriented towards user can be used as a tool to increase awareness of the land subsidence phenomenon in the Bandung Basin.